Justifying Clinical Deception: Some Amendments to Brummett and Salter - Meyers, Christopher 1957- (2023)
In Abram Brummett and Erica K. Salter's excellent paper, “Mapping the Moral Terrain of Clinical Deception,” they rightly note that it is sometimes ethically appropriate for health care professionals to deceive patients and families. However, they also note that because doing so violates a prima facie duty of honesty, the ethical burden of proof falls upon the deceiver. Hence, they also provide a sophisticated framework for determining whether any given case is warranted. I applaud their overall approach but also critique some of their claims, in particular, their conclusion that lies of commission require greater justification than those of omission and their conflation of the principles of beneficence and nonmaleficence. I also urge them to give greater attention to how power asymmetries should be accounted for and to the impact such deceptive choices might have on the clinician's character.
Keywords: clinical ethics; Virtue; Power; Bok; Lying; Deception